Comparable rates of simulator sickness in Huntington's disease and healthy individuals. (January 2019) - Jacobs, Milou; van der Zwaan, Kasper F.; Hart, Ellen P.; Groeneveld, Geert Jan; Roos, Raymund A.C.
Highlights: Older age and female gender are associated with symptoms of simulator sickness. Huntington's disease does not increase the risk of developing simulator sickness. Decreased smooth ocular pursuit is a predictor of dropout due to simulator sickness. Cognitive functioning is unrelated to simulator sickness. Abstract: Objective: Investigating driving competence with a simulator provides a controlled setting and has a high reproducibility. In addition, there is less risk of physical harm compared to on-road tests. A disadvantage of using simulators is the occurrence of simulator sickness, which is comparable to symptoms of motion sickness. The aim of this study was to examine whether patients with Huntington's disease (HD) are more susceptible to develop simulator sickness compared to healthy individuals. Further, we investigated if the clinical symptoms of HD, such as motor disabilities and cognitive deterioration, might increase the occurrence of simulator sickness. Methods: Eighty-three participants (54 HD, 29 controls) drove in a driving simulator that included urban and motorway scenarios. All participants were still active drivers. Motor, cognitive, and oculomotor assessments were administered. Participants completed a questionnaire after the driving session to report possible symptoms of simulator sickness. Results: Fifty-eight (70%) participants completed the driving session, while 25 (30%) participants dropped out due to simulator sickness. The most reported symptoms of simulator sickness by dropouts were difficulties concentrating, dizziness, nausea, sweating, and vomiting. Dropouts were significantly older and more often female compared to completers. Decreased smooth ocular pursuit was predictive of dropout due to simulator sickness. The number of HD participants and controls in the dropout group was comparable. There was no significant difference in cognitive performance and motor functioning between completers and dropouts. Conclusions: HD participants did not have a higher chance of developing simulator sickness while driving in a simulator compared to controls. Female gender, older age, and smooth ocular pursuit were associated with increased simulator sickness, whereas cognitive and motor functioning were unrelated to dropout due to simulator sickness.